Methodologies of comparative philosophy: the pragmatist and process traditions - Smid, Robert W. (SUNY series in Chinese philosophy and culture, 2009)
Introduction: the ballad of East and West -- William Ernest Hocking -- Filmer S.C. Northrop -- David Hall and Roger Ames -- Robert C. Neville -- Revisiting the twain